Avian Influenza a (H5N1) Infection with Respiratory Failure and Meningoencephalitis in a Canadian Traveller - Naheed Rajabali; Thomas Lim; Colleen Sokolowski; Jason D Prevost; Edward Z Lee (Canadian Journal of Infectious Diseases and Medical Microbiology)
In an urban centre in Alberta, an otherwise healthy 28-year-old woman presented to hospital with pleuritic chest and abdominal pain after returning from Beijing, China. After several days, this was followed by headache, confusion and, ultimately, respiratory failure, coma and death. Microbiology yielded influenza A subtype H5N1 from various body sites and neuroimaging was consistent with meningoencephalitis. While H5N1 infections in humans have been reported in Asia since 1997, this is the first documented case of H5N1 influenza in the Western Hemisphere. The present case demonstrated the typical manifestation of H5N1 influenza but, for the first time, also confirmed previous suggestions from human and animal studies that H5N1 is neurotropic and can manifest with neurological symptoms and meningoencephalitis.